Development of the digital infrastructure of the state system of scientific and technical information in 2021-2025 as a new stage in building a knowledge economy in the Republic of Belarus - A. Kosovskiy; I. Matvienko; N. Yunevich (Informaciâ i Innovacii)
The article examines the conditions created in the Republic of Belarus during the construction of the digital economy and the development of the information society. These conditions are recognized as the basis for new topical transformations of the State System of Scientific and Technical Information of the Republic of Belarus (SSSTI) as a key generator of knowledge of the National Innovation System. Scientific and technical information (STI) and the digital transformation of key areas of its collection, processing, and storage are becoming the main development goals of the SSSTI for 2021-2025.